The Global Effects of Subglobal Climate Policies - Christoph Böhringer; Knut Einar Rosendahl; Carolyn Fischer (Verein für Socialpolitik, 2010)
Individual OECD countries are in the process of legislating responses to the challenges posed by climate change. The prospect of rising carbon prices raises concerns in these nations of the impacts on the competitiveness of their own energy intensive industries and the potential for carbon leakage, particularly to emerging economies that lack comparable regulation. As a response, controversial trade-related measures and allowance allocation designs are being proposed to complement their climate policies. Missing from much of the debate on trade-related measures is a broader understanding about how climate policies implemented unilaterally (or sub-globally) affect all countries in the global trading system. Arguably, the largest impacts are from the targeted carbon pricing itself, which generates macroeconomic effects, terms-of-trade changes, and shifts in global energy demand and prices, in addition to changing the relative prices of certain energy-intensive goods. This paper studies how climate policies implemented in certain major economies (the EU and the US) affect the global distribution of economic and environmental outcomes, and how these outcomes may be altered by a variety of complementary policies aimed at addressing carbon leakage.
Keywords: Q43; D61; D58; 330